Improved survival after pancreatic re-resection of positive neck margin in pancreatic cancer patients. A systematic review and network meta-analysis. Issue 6 (June 2021) - Crippa, Stefano; Ricci, Claudio; Guarneri, Giovanni; Ingaldi, Carlo; Gasparini, Giulia; Partelli, Stefano; Casadei, Riccardo; Falconi, Massimo
Abstract: The oncological benefit of achieving a negative pancreatic neck margin through re-resection after a positive frozen section (FS) is debated. Aim of this network meta-analysis is to evaluate the survival benefit of re-resection after intraoperative FS neck margin examination following pancreatectomy for ductal adenocarcinoma. A systematic search of studies comparing different strategies for the management of positive FS was performed. Patients were classified in three groups based on FS and permanent section (PS): Group A (FS-, P S-R0), Group B (FS+, P S-R0), Group C (FS±, P S-R1). A frequent random-effects network-meta-analysis was made reporting the surface under the cumulative ranking (SUCRA). Primary endpoint was overall survival (OS). Secondary endpoints were pathological outcomes. Seven retrospectives studies with 4205 patients were included and 99.1% of the pancreatic resections were pancreatoduodenectomies. Group A had the highest probability of better OS (SUCRA = 90%), compared to Group B (SUCRA = 48.7%) and Group C, which was the worst prognostic scenario (SUCRA = 11.3%). Group B had still a probability of longer OS compared to Group C (SUCRA = 48.7% vs 11.3%). Pathological features were more favourable in Group A, with the highest SUCRA for T1-T2 tumors (92.6%), N0 status (89.4%), absence of perineural invasion (92.3%). Heterogeneity was low (τ-value <0.1) for OS, and moderate (τ-values: 0.1–0.6) for pT, pN, and perineural invasion. In conclusion, negative neck margin after primary resection (FS negative) or re-resection of a positive FS was associated with improved survival compared with P S-R1. However, any intraoperative positive FS can be considered as a prognostic factor associated with a more aggressive disease.